Proyecto de factibilidad para la producción y comercialización de jugo de “Selenicereus undatus” (Pitahaya) en la ciudad de Loja - Alvarado Chamorro, Johana Stefania (2023)
A feasibility project allows us to perform an analysis on the acceptance and viability of a new product in the market, so the project was conducted based on the approach of objectives such as: the market study to determine supply, demand, unsatisfied demand and the marketing plan; the technical study to determine size, location and engineering of the project; the organizational study to determine the legal and administrative structure; the financial study to know the investments, financing, cost and income budgets, financial statements and financial evaluation; the research approach was quantitative, exploratory and descriptive type and scope, the method is deductive, also techniques and instruments were used to collect information; through the demand and supply analysis, the unsatisfied demand was determined to be 1`971,158 units for year 1; the capacity used is 1`168,000 units; the investment required for the implementation of the company is $102,512.4. The production cost for year one is 0.57 cents; with a retail price of 0.65 cents, obtaining a sales revenue of $543,454.81; the break-even point is 38% based on capacity and $207,311 based on sales; the cash flow was made and the evaluation indicators were applied, where the following results were obtained: Net Present Value (NPV) of $ 93. 668.84; Internal Rate of Return (IRR) of 42.73%; Capital Recovery Period of 2 years, 4 months and 13 days; Benefit-Cost Ratio of 1.14; and finally, the Sensitivity Analysis (SA) supporting an increase in costs of 4.7% and a decrease in income of 4.1%. And through this analysis it was determined that the project is feasible